Neurobrucellosis in systemic lupus erythematosus - Jamshid Vafaeimanesh; Alireza Shahhamzeh; Mohammad Bagherzadeh (Babol University of Medical Sciences, 2017)
Background: Brucellosis is a zoonotic infection which is endemic in many countries. It is a multisystem disease which may present with a broad spectrum of clinical manifestations and complications. Neurobrucellosis is an uncommon complication of brucellosis. Case presentation: A 25-year-old woman with a history of lupus for 5 months referred to the emergency ward of Shahid Beheshti Hospital of Qom due to vertigo, drop attack and a convulsion episode from the previous day. She was unable to move at initial evaluation, and her upper and lower extremities were spastic. She had blurred vision one day after admission. Based on her past history and suspecting neurological pulmonary presentations, treatment with immunosuppressive drugs was started and brain MRI was performed. According to the MRI mode and endemic area, neurobrucellosis was suspected and 2ME and Wright tests were performed. Wight test was 1.5120 while 2ME test was 1.640 which were strongly positive. So, with neurobrucellosis diagnosis, the patient was treated but unfortunately 4 days later, after respiratory apnea, she was pronounced dead. Conclusion: In endemic areas for brucellosis, neurobrucellosis should always be kept in mind in the differential diagnosis of neurological and psychiatric cases that are encountered.